(untitled) (Altre Modernità, 2020)
This paper addresses the concept of flotsam in relation to language by examining the non-standard spellings used in a selection of literary representations of the Lancashire dialect written in the Late Modern English period. The analysis is placed within the framework of enregisterment and indexicality, which I explore in combination with recent sociolinguistic approaches to the study of orthography. Attention is paid to two of the frequently occurring features in these speech recreations (l-vocalisation and the rounding of /a/+nasal), arguing that the respellings employed to represent them can be taken as instances of flotsam in that they contribute to highlighting and enregistering linguistic differences.